Da’i dan Pemanfaatan Instagram: Tantangan Moderasi Dakwah di Era Digital - Ni’amah, Luthfi Ulfa; Putri, Sukma Ari Ragil (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2019)
This article discusses the use of social media, especially Instagram, in proselytising activities by preachers in Indonesia and examines Islamic discourse uploaded by native digital preacher, Felix Siauw. Using Teun A. Van Djik's discourse analysis, this study shows that Instagram is one of the social media used by Islamic preachers from native digital generation. In addition, the message of da'wah delivered by Ustadz Felix seems to negate the moderation of da'wah that can threaten the unity and integrity of the nation. Thus, this study recommends that preachers from digital immigrant groups should be actively involved in social media as an effort to develop moderate Islamic da'wah.